Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm a college student and I've got a problem solving this:

$$\frac{2x+3}{x+1} = \frac{2x+2}{x-1}.$$

Since neither the numerators nor the denominators are equal, I figured that $(2x+3)(x-1) = (x+1)(2x+2)$ would provide me with a suitable $x$.

However calculating this I found that $x = -\frac13$ while my answer sheet states that $x = -\frac23$. What am I doing wrong?

share|improve this question
2  
Are you certain you have written the problem correctly? My answer differs both from yours and from the answer sheet. –  AMPerrine Oct 30 '11 at 20:09
    
Thank you for your answers everyone, I'm sorry about the answer from the answer sheet being wrong, it should have been -(5/3) –  Henri Oct 30 '11 at 20:24
    
Hopefully this doesn't sound to condescending, but if you are ever unsure about a solution to an equation, often the easiest thing to do is just substitute the solution back in and see if everything works out. Indeed, it's probably not a bad practice even when you're not unsure about the solution :) –  tom Oct 31 '11 at 0:59

2 Answers 2

up vote 2 down vote accepted

Well you have by cross multiplying that,$$2(x+1)^{2} = 2x^{2} + x -3$$ $$ \Longrightarrow 2x^{2}+4x+2 = 2x^{2} + x -3$$ $$ \Longrightarrow 3x = -5 \Rightarrow x= -\frac{5}{3}$$

share|improve this answer
1  
Oops, The answer sheet answer should be -5/3 indeed, It's just that I wrote it down like this: -1(1/3) it figures that should go wrong. Looking at your anwers, I think I know what I did wrong. I added 2 instead of subtracting it from -3. Subtracting gives 3x = -5 so that's it. –  Henri Oct 30 '11 at 20:23

There’s nothing wrong with your basic approach, but you seem to have solved the equation $(2x+3)(x-1)=(x+1)(2x+2)$ incorrectly. After multiplying out both sides, you should have $$2x^2+x-3=2x^2+4x+2\;,$$ which simplifies progressively to $$\begin{align*} x-3&=4x+2\;,\\ -3&=3x+2\;,\\ -5&=3x\;,\text{ and}\\ x&=-\frac53. \end{align*}$$

Substituting this into the original equation yields $$\begin{align*} \frac{2\left(-\frac53\right)+3}{-\frac53+1} &\stackrel{?}= \frac{2\left(-\frac53\right)+2}{-\frac53-1}\\ \frac{-\frac13}{-\frac23} &\stackrel{?}= \frac{-\frac43}{-\frac83}\\ \frac12&=\frac12. \end{align*}$$

In other words, both you and the answer sheet are wrong.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.